PENGARUH MEDIA PEMBELAJARAN BERBASIS ETNOMATIKA TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH DASAR (KONTEKST BUDAYA SULAWESI SELATAN) - Marian, Ivon; Waddi Fatimah; Eka Fitriana HS; Syamsul Alam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the use of ethnomatics-based learning media on the learning motivation of elementary school students (South Sulawesi cultural context). This study is an experimental study using a quantitative approach. This study took place at the UPT SPF SD Inpres Perumnas Antang III. The population of this study were students randomly selected in classes IV A, IV B, and IV C with sampling using simple random sampling. The sample in this study was 29 students of class IV B consisting of 11 boys and 18 girls. The research instruments used were observation sheets, questionnaires and documentation. Data analysis used descriptive analysis and inferential statistical analysis with the help of the SPSS computer program. The results of this study indicate that the ability of teachers in using ethnomatics-based learning media in student learning obtained an average score of 3.5 which was carried out very well. The learning motivation of fourth-grade students from the results of the prerequisite test consisting of the normality test Pretest 0.295 and Posttest 0.312, the results of the homogeneity test 0.095, and the hypothesis test 0.000. So the results of this study show that the use of ethnomatics-based learning media has an effect on students' learning motivation.